1998
DOI: 10.1242/dev.125.18.3709
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone affects Schwann cell and oligodendrocyte gene expression at the glial transition zone of the VIIIth nerve prior to cochlea function

Abstract: All cranial nerves, as well as the VIIIth nerve which invades the cochlea, have a proximal end in which myelin is formed by Schwann cells and a distal end which is surrounded by oligodendrocytes. The question which arises in this context is whether peripheral and central parts of these nerves myelinate simultaneously or subsequently and whether the myelination of either of the parts occurs simultaneously at the onset of the cochlea function and under the control of neuronal activity. In the present paper, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(9 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…In the mouse cochlea, myelination by Schwann cells starts near birth at the cell bodies of SGNs and progresses to the central and peripheral processes between P8 and P10, just before the onset of hearing ( 65 ). It has been proposed that TRβ is necessary for myelinogenesis of the auditory nerve ( 66 ). In this study, we demonstrated a thickening of the myelin sheath in myelinated ANFs in 1-month-old Thra S1/+ mice.…”
Section: Discussionmentioning
confidence: 99%
“…In the mouse cochlea, myelination by Schwann cells starts near birth at the cell bodies of SGNs and progresses to the central and peripheral processes between P8 and P10, just before the onset of hearing ( 65 ). It has been proposed that TRβ is necessary for myelinogenesis of the auditory nerve ( 66 ). In this study, we demonstrated a thickening of the myelin sheath in myelinated ANFs in 1-month-old Thra S1/+ mice.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroxine affects the development of the nervous system [ 25 ], which is also critical to the development of the inner ear. Early studies reported that the location and function of microtubules could be impacted by F-actin, and the microfilaments could be raised by the intracellular segments of adhesion molecules [ 26 , 27 ]. Thyroxine affects formation of the cytoskeleton, nerve regeneration and degradation of adhesion molecules in the testis [ 28 , 29 ], which indicates that thyroxine plays a similar role in the maturation of the OC.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid is the largest endocrine organ in the human body, and it secretes thyroid hormone, which is necessary to maintain the normal metabolism of the human body and can promote protein synthesis and regulate the metabolism of sugar, fat, water, salt, and vitamins. In addition, thyroid hormones play an important role in the development and maturation of spiral ganglion cells, hair cells, and hearing, formation of nerve myelin, oxygenation, and metabolism of Corti and stria vascularis 10–16 . Hyperthyroidism and hypothyroidism both can affect hearing, such as an increase change in wave V latency in the auditory brainstem response (ABR) and higher audiometric thresholds and TOAEs abnormality 17–19 …”
Section: Introductionmentioning
confidence: 99%
“…In addition, thyroid hormones play an important role in the development and maturation of spiral ganglion cells, hair cells, and hearing, formation of nerve myelin, oxygenation, and metabolism of Corti and stria vascularis. [10][11][12][13][14][15][16] Hyperthyroidism and hypothyroidism both can affect hearing, such as an increase change in wave V latency in the auditory brainstem response (ABR) and higher audiometric thresholds and TOAEs abnormality. [17][18][19] Hashimoto's thyroiditis, with an incidence of 0.3-1.5 cases per 1000 people, is characterized by increased thyroid volume, lymphocyte infiltration of parenchyma, and antibodies specific to thyroid antigens.…”
mentioning
confidence: 99%